Pengaruh Reward System Terhadap Turnover Intention Karyawan Sebuah Tinjauan Sistematis - Novia Komalasari; Nyoman Anita Damayanti (Universitas Malahayati Lampung, 2026)
ABSTRACT Turnover intention, or the intention of employees to leave their jobs, has become one of the biggest challenges for organisations in various sectors. High turnover intention not only leads to the loss of valuable human resources, but also increases the company's operational costs, such as the cost of recruiting, training, and adapting new employees. Several studies prove that there is a relationship between the reward system and turnover intention. This article aims to provide a systematic review of the relationship between reward systems and turnover intention, by evaluating previous research, highlighting key factors, and providing strategic recommendations for organisations. Systematic review based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Articles were searched through Scopus, PubMed and Semantic Scholar with publications from 2020 to 2024. Articles selected were those that met the predetermined inclusion criteria. Of the eleven articles that met the inclusion criteria, it was found that there was a significant relationship between the reward system and employee turnover intention. This is evidenced by the statistical p value 0.05. The effect of the reward system on employee turnover intention is a negative influence, meaning that the better the reward system given to employees, the smaller the employee turnover intention. An organisation or company must design a good reward system to reduce employee turnover intention. Keywords: Reward System, Turnover Intention, Remuneration, Systematic Review. ABSTRAK Turnover intention atau niat karyawan untuk meninggalkan pekerjaannya, telah menjadi salah satu tantangan terbesar bagi organisasi di berbagai sektor. Tingginya turnover intention tidak hanya menyebabkan hilangnya sumber daya manusia yang berharga, tetapi juga meningkatkan biaya operasional perusahaan, seperti biaya perekrutan, pelatihan, dan adaptasi karyawan baru. Beberapa penelitian membuktikan bahwa terdapat hubungan antara reward system dengan turnover intention. Penulisan artikel ini bertujuan untuk menyusun tinjauan sistematis mengenai hubungan antara reward system dan turnover intention, dengan mengevaluasi hasil penelitian sebelumnya, menyoroti faktor kunci, serta memberikan rekomendasi strategis bagi organisasi. systematic review, yang disusun berdasarkan Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Pencarian artikel melalui Scopus, PubMed dan Semantic Scholar dengan penerbitan mulai tahun 2020 sampai 2024. Artikel yang dipilih adalah artikel yang sesuai dengan kriteria inklusi yang telah ditetapkan. Dari sebelas artikel yang masuk kriteria inklusi didapatkan hasil bahwa terdapat hubungan yang signifikan antara reward system dan turnover intention karyawan. Hal ini dibuktikan dengan statistik nilai p value0.05. Pengaruh reward system terhadap turnover intention karyawan adalah pengaruh yang negatif, artinya semakin baik reward system yang diberikan kepada karyawan maka semakin kecil turnover intention karyawan. Suatu organisasi atau perusahaan harus merancang reward system yang baik untuk menurunkan turnover intention karyawan. Kata Kunci: Reward System, Turnover Intention, Remuneration, Systematic Review.